SOUTHERN BLUEFIN TUNA (Thunnus maccoyii) CAUGHT BY INDONESIA’S TUNA LONGLINERS IN THE SPAWNING AREA - Fathur Rochman; Watiniasih Ni Luh; Yuni Luh Putu Eswaryanti Kusuma (Indonesian Fisheries Research Journal, 2019)
Southern Bluefin Tuna in spawning area of the Eastern Indian Ocean where the Indonesian’s longliners operated has a specific character in term of size, age, sex-specific growth rate and the population. The aims of this study are to determined changes in size/age, sex-specific growth rate and virtual population analysis of Southern Bluefin Tuna (SBT) in the spawning area. This study is important to find out the successful management of SBT in spawning area by looking at the catch at age/size movement, sex-specific growth analysis and the estimation of the population by virtual population analysis. In this study, we were used 452 pairs of otolith with fish sized from 134-196 cmFL and fish aged from 8-20 years. The growth equation was Lt = 191 (1-e-0,167(t+1,081)). Catch at age structure was distributed from 5-22 years with mean and mode of age were 9.63 and 9 years. The distribution of mode changed from year to year shifting to a younger fish. In 2012, the mode was 10 years but entering 2013-2014 the mode was shifted to 6 years. In 2015-2017, the mode was increased from 7 years (2015) to 8 years (2016) and 9 years (2017). The fishing pressure happened in the age group under 20 years. In 2012 to 2014, the highest fishing pressure respectively obtained in the age group of 13 to 11 years with an average length of 167 to 174 cmFL. Entering 2015 and 2016, the highest fishing pressure obtained in the age group of 6 years with an average length of 138 cmFL. The exploitation rate ranged from 0.14/year to 0.25/year meaning that the exploitation was in optimal condition.